2019
DOI: 10.1177/0301006619867865
|View full text |Cite
|
Sign up to set email alerts
|

“There Is NoFaceLike Home”: Ratings for Cultural Familiarity to Own and Other FacialDialectsof Emotion With and Without Conscious Awareness in a British Sample

Abstract: The dialects theory of cross-cultural communication suggests that due to culture-specific characteristics in the expression of emotion, we can recognise own-culture emotional expressions more accurately than other-culture emotional expressions. This effect is suggested to occur due to the nonconvergent social evolution that takes place in different geographical regions. Based on the evolutionary value of own-culture social signals, previous research has suggested that own-culture emotional expressions can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 78 publications
2
27
0
Order By: Relevance
“…During this study, two important hypotheses were tested in relation to password memorability: the effect of selected images from one’s own culture, and the cultural influence on the decay of password memorability. This study found that selecting images based on cultural familiarity improves a password’s memorability, such observation in compliance with (Tsikandilakis et al , 2019). Cultural designs that rely on such images may improve users’ cognition and memorization of the password.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…During this study, two important hypotheses were tested in relation to password memorability: the effect of selected images from one’s own culture, and the cultural influence on the decay of password memorability. This study found that selecting images based on cultural familiarity improves a password’s memorability, such observation in compliance with (Tsikandilakis et al , 2019). Cultural designs that rely on such images may improve users’ cognition and memorization of the password.…”
Section: Discussionsupporting
confidence: 77%
“…To address this issue and its influence on graphical password effectiveness, this study examines the central research question: Does selecting images based on cultural familiarity improve the memorability of the password over time? “Cultural familiarity” refers to the conscious awareness of other cultures (Tsikandilakis et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Results and Discussion: Confidence, Click Pressure, Release Time, and Subliminality Signal detection analysis for faces presented for 13.89 ms revealed a trend for Bayesian evidence for the null-that detection performance was within a priori defined criteria for chance-level performance-suggesting that these stimuli could have been processed subliminally (M ¼ 0.5113, SD ¼ 0.0436, SE ¼ 0.0063, B ¼ 0.39). To explore responses to subliminal emotional faces and also whether the current technology could be used for the physiological assessment of subliminal emotion, we used the analysis model for the assessment of subliminality described in previous publications Tsikandilakis et al, , 2019bTsikandilakis et al, , 2019cTsikandilakis et al, , 2019dTsikandilakis, Kausel, et al, 2019). To explore whether was calculated for mean differences to the average condition mean and standard error for that condition (see Table 3) to test evidence for the null (B < 0.33; Dienes, 2014Dienes, , 2016.…”
Section: Results and Discussion: Varying Intervals: Force Pressure And Click-release Timementioning
confidence: 99%
“…In a previous publication we contested this notion (Tsikandilakis, Kausel, Boncompte, et al, 2019; see also Amihai et al, 2011). We created and validated a facial dataset with freely-expressed and Facial Action Units Coding System (FACS; Ekman et al, 2002) instructed emotional expression using actors from Britain, Chile, New Zealand and Singapore (Tsikandilakis, Kausel, Boncompte, et al, 2019, pp.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that a single glimpse could be sufficient to allow us to evaluate whether a face and/or emotional expression originated from our own cultural background. It also suggested that conscious perception and meta-awareness, such as reporting seeing a presented masked face during a post-trial task (see Bargh and Morsella, 2008), were involved in the appraisal of cultural dialects of emotion (see also Tsikandilakis, Kausel, Boncompte, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%